Dual stereocontrolled alkylation of aldehydes with polystyrene-supported nickel complexes derived from α-amino amides. Issue 19 (30th January 2015) - Escorihuela, Jorge; Altava, Belén; Burguete, M. Isabel; Luis, Santiago V.
Abstract : Nickel(ii ) complexes derived from α-amino amide ligands anchored to gel-type and monolithic polymers act as efficient catalysts for the enantioselective addition of dialkylzinc reagents to aldehydes. Abstract : Nickel(ii ) complexes derived from α-amino amide ligands anchored to gel-type and monolithic polymers act as efficient catalysts for the enantioselective addition of dialkylzinc reagents to aldehydes. Similar to the analogous homogeneous systems, dual stereocontrol in addition products can be achieved by controlling the stoichiometry of the immobilized nickel complex. Aromatic and aliphatic aldehydes were alkylated in good yields with enantioselectivities comparable to those obtained with the homogeneous analogues. These polymer-supported catalysts offer significant advantages as no metal leaching is observed and they can be easily recovered from the reaction mixture by simple filtration and reused for subsequent experiments with consistent catalytic activity.